1982
DOI: 10.1055/s-2008-1056251
|View full text |Cite
|
Sign up to set email alerts
|

Erste klinische Erfahrungen mit einem neuen Großbildverstärker in der Thoraxdiagnostik

Abstract: In 350 patients with 870 pathologic findings comparative blind analysis of conventional chest films and biplane 100 mm photofluorographic images taken with the large-field image intensifier revealed high accuracy in the evaluation of coin lesions, hilar and pleural pathology, pulmonary vasculature and the right paratracheal stripe. Moderate central interstitial edema, more subtle interstitial changes particularly in the lung periphery including Kerley's B-lines, and calcifications in the hilum or the aortic ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

1983
1983
2001
2001

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…NEUFANG et coIl. (13) found that in photospot films, moderate central interstitial edema and more subtle interstitial changes, particularly in the lung periphery, including Kerley's B-lines were not always visible. However, a contributing cause may be the film viewer used.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…NEUFANG et coIl. (13) found that in photospot films, moderate central interstitial edema and more subtle interstitial changes, particularly in the lung periphery, including Kerley's B-lines were not always visible. However, a contributing cause may be the film viewer used.…”
Section: Discussionmentioning
confidence: 90%
“…(13) and RAITHEL et coll. (14) about the lack of definition in peripheral areas, especially in stout patients, and which was expressed in our work as poorer visibility of the finest vascular branches, and the lung apices on the lateral radiographs (Table 4), is evidently a consequence of a reduction in resolving power and density in field periphery (Fig.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Preliminary investigations on large-image intensifier photofluorography in chest radiography have shown promising results, although inferior definition in the peripheral image field has been noted (6,10,12,14). In these studies, conventional chest radiography has been used as the reference technique, but the final value of this new imaging modality can be tested only in conjunction with clinical search for individual diseases using a separate and more accurate reference technique.…”
Section: Discussionmentioning
confidence: 99%
“…The spatial resolution of II photofluorography is only 70 to 90 per cent of that of most screen-film combinations used in chest radiography, and there is moderate electron-optical distortion in the peripheral image field (10). Good visualization of diagnostically important anatomic details in central parts of the chest have been reported in the preliminary studies on this imaging modality (10,12). Poorer visualization has been found in the peripheral field in comparison with conventional chest radiography.…”
mentioning
confidence: 99%